Secondary Polycythemia in Hepatocellular Carcinoma: Treat or No Treat - Poernomo Budi Setiawan; Ummi Maimunah; Nenci Siagian (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2020)
A 45-year man with a chronic hepatitis B virus (HBV) infection, elevated alphafetoprotein (AFP) 628ng/dL and Abdominal CT-scan features of Hepatocellular Carcinoma was admitted with polycythemia condition (haemoglobin 20.4g/dL, haematocrit 65.4%). Elevated of erythropoietin (EPO) serum level confirmed the polycythemia was because of hepatocellular carcinoma (HCC) as a paraneoplastic syndrome. Based on diganosis criteria of HCC by Indonesian Association for the Study of the Liver 2017, the patient was diagnosed with HCC Barcelona clinic liver cancer (BCLC) B and was treated with trans arterial chemotherapy and embolization (TACE) with mixed doxorubicin. Aspirin 80mg once daily was given to patient to prevent thrombosis event. One month later after TACE, haemoglobin and haematocrite didn’t improve. Then 4 months later the patient died of cardiovascular event in the last admission at district hospital.